Quels discours sur les crimes nazis dans la chronique judiciaire ouest‑allemande des années 1950 ? Le procès du camp du Stutthof à Bochum en 1955 vu par la presse locale et régionale - Nathalie Le Bouëdec (Criminocorpus)
Although the desire to draw a line under the Nazi past was still dominant in West Germany in the 1950s, the subject of Nazi crimes was not absent from the public arena, especially at the local level. This is shown in this micro-historical case study, which analyses the media coverage of the Stutthof camp trial in Bochum at the end of 1955 in the local and regional press. The overall lack of criticism and perspective on the trial (with the notable exception of the communist press) is certainly striking. Nevertheless, the newspapers provided a lot of information on the fate of the prisoners and the extermination of the Jews and confronted their readers with the testimonies of the victims and the atrocities committed in the Stutthof. The court reports contained elements that could have led to a critical reflection on the Nazi past, the conditions for this to happen were not yet really in place, neither on the part of the press nor on the part of its readership.